Encyclopedia of Microbiology:Vol-1. - Lederberg, Joshua;Ed (Academic Press, 2000)
Challenges the reader, and illustrates the importance of microbiology. This four-volume set contains approximately 300 articles, 1000 illustrations, and 400 tables, providing color plate sections. It covers 17 subject areas, including coverage of microbes in extreme environments and microbes in emerging infections.